Factores relacionados a partos por cesárea en el Hospital II EsSalud de Huánuco - Huamán Santillán, Abner (2018)
Introduction: The objective of the present study was to determine the frequency of caesarean in the EsSalud Hospital II - Huánuco and identify related factors. Methods: Cross-sectional descriptive design study. The dependent variable was “type of childbirth” and the independent variables included clinical and non clinical characteristics. To obtain data records were used. We performed a bivariate analysis of clinical variables, using chi-square and Fisher's exact test was associated with ratio prevalence (RP), the statistical analysis of the non clinical variable was performed using Pearson correlation. Results: The rate cesarean obtained was 37.16%, found association between cesarean and previous cesarean variables [p = 0.000, OR: 2.81 (CI: 2.12 to 3.72)], fetal presentation [p = 0.034 , PR: 2.14 (CI: 1.37 to 3.34)], premature detachment of placenta [p = 0.039, OR: 2.61 (CI: 1.73 to 3.94)], acute fetal distress [p = 0.000, OR: 2.68, (CI: 1.99 to 3.60)], premature rupture of membrane [p = 0.011, OR: 1.76 (CI: 1.20 to 2.58)], placenta previa (p = 0.013, OR: 2.71 (CI: 1.92 to 3.82)] and disturbance of amniotic fluid (p = 0.012, OR: 1.90 (CI: 1.26 to 2.88) ]; are not statistically significant variables fetal macrosomia, pregnancyinduced hypertension, treatment for infertility, multiple pregnancy and condilomatosis. The non clinical variable “doctor” was not significant. Conclusions: Rate of cesarean in the EsSalud Hospital II-Huánuco was 37.16%, and factors related to cesarean were previous cesarean, fetal presentation, premature detachment of placenta, acute fetal distress, premature rupture of membranes, placenta previa and disturbance of liquid amniotic fluid.